The institutional pluralism of the state - Holperin, Michelle Moretzsohn (2017)
What are the logics that public organizations enact in their daily activities? This doctoral dissertation investigated the institutional logics of the State. The institutional logic concept adopted was the one of Friedland and colleagues: institutional logics are 'stable constellations of practice', the necessary coupling of substances and material practices that constitutes the institutions’ organizing principles (Friedland et.al., 2014). The State is understood as one of the central institutions of society, composed by two dimensions. One is the bureaucratic dimension, permeated by different ideas about how things should be done in the State. The other is the capitalist dimension, permeated by different ideas about what should be done,i.e., what should be the role of the State. I have chosen a specific type of public organization to explore the logic of the State: the Brazilian independent regulatory agencies (IRAs). IRAs have diffused widely in the past years, and the literature suggests that they represent the 'appropriate model of governance' of the capitalist economy (Levi-Faur, 2005). They changed both how things were done - emphasizing the state's rule-making instruments - and what should be done - focusing on competition promotion and correcting market failures (Majone, 1994). In Brazil, IRAs were part of a broader process of State Reform, and represented an important innovation in terms of organizational design, based on autonomy, and role to be performed, based on competition promotion. However, the process of IRAs’ diffusion was largely impacted by the local context and despite being idealized as purely regulatory, their policies and activities indicate that they do much more than promoting competition. In fact, state policies in general, and regulatory policies in particular, 'are rooted in changing conceptions of what the state is, what it can and should do' (Friedland & Alford, 1991). To assess the institutional logics of the State, this research investigated over 9,000 press releases published by three formal independent regulatory agencies in Brazil between 2002 and 2016. Those press releases cover all the news they released since their creation. Press releases are frequently used by Brazilian IRAs, and they serve as a good proxy of the policies and activities conducted by these agencies. I applied a correlated topic model (CTM) to extract the main themes discussed by the agencies in the past years. Originating from the study areas of natural language processing and machine learning, topic models are probabilistic models that uncover the semantic structure of a collection of documents, or corpus (Blei, 2012; Blei, Ng & Jordan, 2003). Differently from other content analysis techniques, topic models are purely inductive and conform to the ‘relationality’ of meaning assumption of the institutional logics literature (DiMaggio, Nag & Blei, 2013). The results indicated that the logics enacted by independent agencies do not refer only to procedural correctness (Meyer & Hammerschmid, 2006) or democracy (Ocasio, Mauskapf & Steele, 2015). In fact, much of what they do is grounded on broader substantive values, reflecting developmental-, pro-competition- and social-oriented interpretations of the role of the State. Yet, the bureaucratic logic is very pervasive within IRAs: it permeates substantive logics, but also it stands up as a logic of its own. Regulatory agencies enact it more often when they are not able to perform their substantive mission. IRAs re-frame at their discretion the practices of administrative police (standards setting and inspections) and public participation (procedural fairness) during periods of crisis, in order to justify their actions. By doing so, they were able to legitimate their existence, gain a new sense of mission and avoid blame for their actions.